Kedudukan Kejaksaan di Indonesia: Perspektif Fiqih Siyasah - Ferdika, Ario Feby; Mu’in, Fathul; Latua, Abidin; Hendriyadi, Hendriyadi (Universitas Islam Negeri Raden Intan Lampung, 2022)
Law Number 16 of 2004 concerning the Attorney General's Office places the prosecutor's office as an executive body, but Law Number 48 of 2009 concerning judicial power places the position of the prosecutor as a judicial body. In Islamic law, the position of the prosecutor's office is not clearly explained, but the position of the prosecutor's office can be likened to the wilayah al-hisbah. However, the position of the prosecutor's office in Indonesia is still not in accordance with the rules of Islamic law. This study aims to determine the position of the prosecutor in the institutional structure of the Indonesian state and analyze it from the perspective of siyasah fiqh. This research is a normative legal research using secondary data in the form of primary, secondary and tertiary legal materials. This study concludes that the position of the Prosecutor's Office is one of the state institutions which is not clearly explained in the siyasa dusturiyah, but the duties and functions of the Prosecutor's Office in general can be similar to the wilayah al-hisbah. The Prosecutor's Office in the general court can be found in Islamic courts, namely the Al-Hisbah Area, or it can also be called in modern language Qadha' Hisbah. Al-Hisbah Territory is a body that adjudicate violations of shari'a outside the court, not because of demands from the prosecution, but because of violations. Although in some respects, the Al-Hisbah Region and the prosecutor's office have differences in some tasks and places to adjudicate a case. Where in the wilayah al-hisbah tried him outside the court, while the Prosecutor's Office tried him in the trial or court.